Efeitos renais e mecanismos de morte celular promovidos pelo veneno da serpente Bothropoides pauloensis - Marinho, Aline Diogo (2013)
According to the Ministry of Health of Brazil, Bothrops are the main involved in snakebites in the country and acute kidney injury is a serious complication of poisoning by these snakes. In this work, we investigated the renal effects of total venom Bothropoidespauloensis (VBP) in isolated rat kidney system and in cultured renal tubular cell line MDCK (Madin - Darby Canine Kidney). For perfusion of isolated kidney Wistar rats were used weighing 250- 300g, whose kidneys were surgically excised and perfused with Krebs- Henseleit solution containing 6% w/v pre-dialysed bovine serum albumin. The effects of VBp (n = 3μg/mL and 10 mg/mL; n=6) was investigated. Reduction was observedin perfusion pressure (PP) at a concentration of 10μg/mL at 90 and 120 min. Renal vascular resistance (RVR) also decreased the concentration of 10μg/mL at 90 and 120 minutes and at a concentration of 3 mg/mL at 120 min. The urinary flow (FU) decreased at 90 and 120 minutes in both concentrations, no significant difference between the concentrations at the time of 120min. The glomerular filtration rate (GFR) was reduced to 60 minutes in both concentrations and remained decreased until the end of the experiment, no significant difference between the concentrations in the time of 60min. The percentage of tubular sodium transport (%TNA+) was reduced by both concentrations in times of 60, 90 and 120 min, with no significant difference between the concentrations at time 60 min. The tubular transport of chloride (%TCl-) was also reduced to 60, 90 and 120 min. In both concentrations; the tubular potassium transport (%TK+) decreased at 60, 90 and 120 minutes at a concentration of 10μg/mL in a concentration of 3μg/mL reduced to 60 min, returning to near control at 90 and 120min values. No significant difference between the concentrations in the times of 60 and 90 min. The analysis showed the presence of significant morphological changes such as the accumulation of proteins plate level in the culture of MDCK cells, the VBP was able to reduce cell viability (IC50 = 7.5 g/ mL). Flow cytometry with Annexin V and propidium iodide showed that cell death occurred by apoptosis predominantly. VBP treatment ( 7.5 mg/ml) led to a significant depolarization of the mitochondrial membrane potential. We verified the generation of Reactive Oxygen Species. Morphological analysis of the cells showed features indicative of apoptosis. These results demonstrate that the venom of B. pauloensis altered all renal parameters evaluated in the kidney perfusion was cytotoxic to isolated and MDCK cell culture.